Edmodo as Web-Based Learning to Improve Student’s Cognitive and Motivation in Learning Thermal Physics - Pia Fildzah Vania; Wawan Setiawan; Agus Fany Chandra Wijaya (Journal of Science Learning, 2018)
This research aims to investigate the use of Edmodo as web-based learning in learning thermal physics in junior high school. The analysis of this research focused on students’ cognitive and motivation in the classroom. The method used in this research was quasi-experiment with the pretest-posttest design. One class taken as a sample in this research comes from one of an international school in Padalarang. The quantitative data of this research was gained through the objective test (pretest-posttest) based on Bloom's Taxonomy and questioner of motivation based on ARCS Motivational Design. Data processing was done by SPSS 20.0. The result of this research shows that there is an improvement of student cognitive C2 until C5 after learning using Edmodo. The average score in pretest was 45.89 and improve to 72.63. The result of normalized gain was 0.49, it included as a medium improvement. Edmodo also increases student motivation in learning thermal physics.